2019
DOI: 10.4103/jmas.jmas_196_18
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic repair of Spigelian hernia with undescended testis

Abstract: Spigelian hernia is very rare in the paediatric age group. We present the case of an 11-month-old male child who presented with left Spigelian hernia with the left undescended testis in its sac. Hernia repair with orchidopexy was done using total laparoscopic approach. It is the first reported case of total laparoscopic repair of Spigelian hernia with undescended testis in the paediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 17 Deshmukh et al reported successful results with laparoscopic orchidopexy and repair for spigelian hernia-ectopic testis. 17 However, more data are required to definitively recommend complete laparoscopic repair vs the conventional open approach. Hence, as a prudent approach, we recommend that this type of case be approached laparoscopically and converted to an open approach if required, depending on the complexity of operative findings and the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Deshmukh et al reported successful results with laparoscopic orchidopexy and repair for spigelian hernia-ectopic testis. 17 However, more data are required to definitively recommend complete laparoscopic repair vs the conventional open approach. Hence, as a prudent approach, we recommend that this type of case be approached laparoscopically and converted to an open approach if required, depending on the complexity of operative findings and the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
“…In uncomplicated cases, complete laparoscopic repair may be a viable option. 17 Deshmukh et al reported successful results with laparoscopic orchidopexy and repair for spigelian hernia-ectopic testis. 17 However, more data are required to definitively recommend complete laparoscopic repair vs the conventional open approach.…”
Section: Discussionmentioning
confidence: 99%
“…Management of SH is surgical through open technique or laparoscopic modalities [7,[13][14][15]. The laparoscopy is considered a new approach according to three cases reported by Kumar et al, Desmukh et al, and Khan et al [12,16,17]. As our case presented with signs of acute intestinal obstruction, we preferred to do an open surgery to manage the case; after opening the sac, which contained fluid, small bowel loops, and the testis, the bowel was healthy, but the testis looked ischaemic.…”
Section: Discussionmentioning
confidence: 99%